2013
DOI: 10.1088/0953-8984/25/39/395601
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic collective electronic mode and low temperature hybrid modes in the far infrared dynamics of orthorhombic NdMnO3

Abstract: We report on far-and mid-infrared reflectivity of NdMnO 3 from 4 K to 300K. Two main features are distinguished in the infrared spectra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 64 publications
(164 reference statements)
3
10
0
Order By: Relevance
“…For instance, the mode at 379 cm −1 could be associated with B 2u mode expected at 388 cm −1 or with B 1u mode at 367 cm −1 . Nevertheless, the ω TO of the observed phonon modes are found in good agreement with those reported for the materials with approxilar crystal structure like polycrystalline NdMnO 3 [16], LaMnO 3 [17] and single crystal GdMnO 3 polarized along a-axis [13], as summarized in Table III. As for the microscopic motion of the phonon modes is concerned, the phonon modes at 85, 116, 169, 187, and 242 cm −1 involve the motion of Gd atoms relative to MnO 6 octahedra. The Gd atoms, being heavier in the GdMnO 3 system, vibrate at low frequency.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…For instance, the mode at 379 cm −1 could be associated with B 2u mode expected at 388 cm −1 or with B 1u mode at 367 cm −1 . Nevertheless, the ω TO of the observed phonon modes are found in good agreement with those reported for the materials with approxilar crystal structure like polycrystalline NdMnO 3 [16], LaMnO 3 [17] and single crystal GdMnO 3 polarized along a-axis [13], as summarized in Table III. As for the microscopic motion of the phonon modes is concerned, the phonon modes at 85, 116, 169, 187, and 242 cm −1 involve the motion of Gd atoms relative to MnO 6 octahedra. The Gd atoms, being heavier in the GdMnO 3 system, vibrate at low frequency.…”
Section: Resultssupporting
confidence: 86%
“…It was also observed that the spectral signature of EuMnO 3 and GdMnO 3 is very approxilar and overall spectra do not change with temperature. Moreover, temperature dependent far-infrared reflectivity of polycrystalline NdMnO 3 have been investigated [16]. It was observed that no new phonon has been detected, so the number of modes remains unchanged in the whole low temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…8 (a)) where, although not having substructure, it is also associated with zone center magnons. [37] The TA gap opening is symmetry dependent on spin and phonon dispersions and only when there is band crossing as in YMnO 3 [17] Our results presents another view of a second order transition in strongly correlated oxides for which the long-range macroscopic view given by Xray patterns, and described by a lattice space group, is not required to change.…”
Section: Spin-likementioning
confidence: 61%
“…7, appears as a room temperature smooth strong tail below 100 cm -1 . [37,38] We found that on cooling the profile change as a consequence of gradually localizing electrons inducing long-range magnetic order. The net electric Peaking at 26 cm -1 the band at lower frequency is Rare Earth dependent.…”
Section: Iv) Thz Hybrid Soft Modesmentioning
confidence: 99%
See 1 more Smart Citation